2015
DOI: 10.1186/s12929-015-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of polyunsatutared fatty acids supplementation against testicular damage induced by intermittent hypobaric hypoxia in rats

Abstract: BackgroundIntermittent hypobaric hypoxia (IHH) induces changes in the redox status and structure in rat testis. These effects may be present in people at high altitudes, such as athletes and miners. Polyunsaturated fatty acids (PUFA) can be effective in counteracting these oxidative modifications due to their antioxidants properties. The aim of the work was to test whether PUFA supplementation attenuates oxidative damage in testis by reinforcing the antioxidant defense system. The animals were divided into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…In particular, Castillo et al . showed that intermittent hypobaric hypoxia induces a pro‐oxidant state in plasma and rat testes through increased lipid peroxidation and reduced in antioxidant mechanisms (Castillo et al ., ). Also, Farias and colleagues asserts that, in testis and epididymis, intermittent hypobaric hypoxia (IHH) induced lipid peroxidation (TBARS production) with a reduction in glutathione reductase activity and a significant decrease in epididymal sperm count (Farias et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…In particular, Castillo et al . showed that intermittent hypobaric hypoxia induces a pro‐oxidant state in plasma and rat testes through increased lipid peroxidation and reduced in antioxidant mechanisms (Castillo et al ., ). Also, Farias and colleagues asserts that, in testis and epididymis, intermittent hypobaric hypoxia (IHH) induced lipid peroxidation (TBARS production) with a reduction in glutathione reductase activity and a significant decrease in epididymal sperm count (Farias et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…After this period, male fertility normalizes, with normal seminal count parameters, motility, form and maturity of spermatozoids [43]. The findings of our group related with the effects of ICH on male fertility has taken us to consider the specific activation of "ICH" pathways, that in conjunction with other variables such as temperature, vascularization and apoptosis, would be involved in the adverse effects on fertility of individuals intermittently exposed to HA [37,44].…”
Section: Reproductive Responses and Treatmentmentioning
confidence: 87%
“…One potential alternative is to incorporate food with high antioxidant levels to the diet in those people exposed to HA, and we have shown that this may have a positive effect in the protection of cells facing oxidative stress [45]. We described, in rats exposed to ICH, that testicles and epididymis shown an increase in lipid peroxidation markers and lower GSH levels compared with normoxic normobaric animals, and that these effects were fully reverted with concomitant administration of ascorbic acid, blueberry extracts or Ω3 chronic supplementation [44,45,46]. Indeed, these protective effects can be supported by the induction of enzymatic and non-enzymatic antioxidant defense systems.…”
Section: Reproductive Responses and Treatmentmentioning
confidence: 89%
“…After euthanasia, cardiac tissue was frozen in liquid nitrogen and stored at −80 °C until use. After tissue homogenization, Western blot (WB) analyses were performed for the protein expression of 4 HNE; specific antibody ab46545 (Abcam Laboratories, Cambridge, UK), Nitrotyrosine (NT, anti-NT 05-233, Millipore, Billerica, MA, USA) as described previously [ 16 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the mechanism that support the precondition effects of acute IH on myocardial and vascular function have not been well characterized. The aim of this work is to describe the responses on cardiac and vascular function, structure and biomechanical properties after four cycles of intermittent hypobaric hypoxia (IHH) and the association with pro oxidant markers and ROS sources in a well-established rat model [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%